Response of broiler chickens to substitution of vitamin-mineral premix with Carica papaya seed meal - M. D. Olumide; A. O. Akintunde; P. Kolu (Diponegoro University, 2022)
The study investigated the physiological response of broiler chickens to substitution of commer-cial vitamin-mineral premix with Carica papaya seed meal (CPS). Two hundred and twenty four (224) mixed sexes Abor – acre day old chicks were subjected to trial for 6 weeks. Data were collected on performance, haematology, serum biochemistry, serum electrolytes and organ morphology. The birds were randomly assigned to 7 dietary treatments: T1: control with commercial vitamin-mineral-premix (VMP) at 0.3% only, T2, 0.05% CPS + 0.25 VMP, T3 0.20 VMP + 0.1 CPS, T4 0.15 VMP + 0.15 CPS, T5 0.10 VMP + 0.2 CPS, T6 0.05 VMP + 0.25 CPS and T7 0.3 CPS. Treatments composed of 4 replica-tions with 8 birds per replicate. Results indicated that significant differences (p<0.05) were observed in all the treatments for WG, FCR and FI. Birds fed with 0.3% of CPS had the best FCR. At the starter phase, significant differences (p<0.05) were observed in the haematology of the birds, however, the values obtained for hemoglobin, white blood cell and eosinophils were not significantly different (p>0.05) while at the finisher phase, the inclusion of Carica papaya seed meal significantly influenced (p<0.05) the values of haematology, the values were however higher (p<0.05) at higher levels of inclu-sion except for white blood cells (WBC) and platelets counts that the control group had significantly higher (p<0.05) values. There was no significant difference (p>0.05) in serum biochemistry parameters at the starter phase except for alanine transaminase (ALT) with significantly higher (p<0.05) value at the control but significantly affected (p<0.05) all the serum biochemical parameters at the finisher phase. Birds fed CPS had significantly higher (p<0.05) values for glucose, cholesterol and low density lipoprotein (LDL). However, birds fed 0.20% CPS had significant highest (p<0.05) values for ALT, Alanine phosphatase (ALP), glucose, cholesterol, LDL and high density lipoprotein (HDL). CPS sig-nificantly influenced (p<0.05) serum electrolytes. Birds in 0.05 and 0.10% CPS inclusion groups had significantly higher (p<0.05) values for sodium, chloride and bicarbonate ions when compared to the control. There was no significant difference (p>0.05) for kidney, liver and spleen. The use of CPS did not impair nutrient utilization neither does it have any adverse effect on the health status of the broiler chickens, hence the use of CPS may be considered as substitute for vitamin-mineral premix in broiler chickens nutrition.